Do farmers care about rented land? A multi-method study on land tenure and soil conservation - Heidi Leonhardt; Klaus Salhofer; Marianne Penker (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2018)
Does ownership status of agricultural land determine farmers' soil use behaviour? Why (not)? We investigate this old question using multiple methods and data. We apply econometric analysis to plot-level data to determine whether planting decisions differ between rented and owned plots. In addition, we analyse interviews with Austrian farmers with the aim of explaining (a lack of) differences. We find a very small influence of tenancy on crop choice in the quantitative part of the study, and qualify these findings in the qualitative part. If at all, interviewed farmers treat rented and owned land differently primarily with respect to fertilization or liming, particularly if the rental is insecure or short-term. We find that renting is often perceived as long-term and secure in Austria, resulting in equal soil conservation behaviour on rented and owned plots. Personal relationships between renter and landowner as well as farmers' attitudes additionally support soil conservation.
Keywords: Q15; Q24; 330; property rights; land ownership; land rental; soil conservation; farmer behaviour